Demoralization in Patients With Substance Use and Co-Occurring Psychiatric Disorders. Issue 2 (3rd April 2017) - De Weert, Gerdien H.; Markus, Wiebren; Kissane, David W.; De Jong, Cornelis A. J.
ABSTRACT: Objective : In recent years, treatment of substance use disorder has rekindled emphasis on recovery which, being a gradual process, starts with remoralization. In this study, we examine the level of demoralization throughout the treatment process for patients with comorbid substance dependence and psychiatric disorders.Methods : 217 patients with co-occurring disorders and 179 community-based individuals participated in this study. Demoralization was measured twice over one month as inpatient treatment happened.Results : In contrast with the community sample, we found high levels of demoralization in the clinical cohort, with 86% of patients having demoralization scores above threshold. During the first month there was a statistically significant reduction in demoralization scores. However, clinically relevant change appeared limited, with only 3% of patients moving from dysfunctional to functional status in this naturalistic setting without targeted intervention aimed at remoralization.Conclusions : Although the level of demoralization is significantly improved during the first month of treatment, patients still remain strongly demoralized. Clinically relevant improvement is limited. It could be worthwhile to set up targeted interventions aimed at remoralization. Furthermore, we advocate for the assessment of demoralization in the clinical setting to monitor patients' treatment outcomes.